2023
DOI: 10.3390/microorganisms11020242
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Spent Coffee Ground Extracts

Abstract: Coffee is one of the most popular and consumed products in the world, generating tons of solid waste known as spent coffee grounds (SCG), containing several bioactive compounds. Here, the antifungal activity of ethanolic SCG extract from caffeinated and decaffeinated coffee capsules was evaluated against yeasts and filamentous fungi. These extracts had antifungal activity against Candida krusei, Candida parapsilosis, Trichophyton mentagrophytes, and Trichophyton rubrum, all skin fungal agents. Moreover, SCG ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Martinez et al (2017) mentioned that chlorogenic acid totally inhibited mycelium growth and spore germination of S. sclerotium, F. solani, V. dahliae, B.cinerea and C. sojina. More recently, Calheiros et al (2023) reported that chlorogenic acid caused chitin, glucan and ergosterol reduction of the cell wall and the cell membrane of C. paropsilosis. Li et al (2017) showed that gallic acid inhibits the ergosterol biosynthesis of T. ruburum.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al (2017) mentioned that chlorogenic acid totally inhibited mycelium growth and spore germination of S. sclerotium, F. solani, V. dahliae, B.cinerea and C. sojina. More recently, Calheiros et al (2023) reported that chlorogenic acid caused chitin, glucan and ergosterol reduction of the cell wall and the cell membrane of C. paropsilosis. Li et al (2017) showed that gallic acid inhibits the ergosterol biosynthesis of T. ruburum.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al [50] mentioned that chlorogenic acid totally inhibited mycelium growth and spore germination of S. sclerotium, F. solani, V. dahliae, B. cinerea and C. sojina. More recently, Calheiros et al [51] reported that chlorogenic acid caused chitin, glucan and ergosterol reduction of the cell wall and the cell membrane of C. paropsilosis. Li et al [52] showed that gallic acid inhibits the ergosterol biosynthesis of T. ruburum, while Bitencourt et al [53] mentioned that quercetin reduces the ergosterol levels of T. ruburum.…”
Section: Discussionmentioning
confidence: 99%
“…The ergosterol extraction and quantification was carried out in 15 mg of the fungal samples previously prepared with the alcoholic KOH method following the protocol described previously [81] with minor modifications [82]. The spectral absorbance range between 220 and 300 nm was obtained in a plate reader using a SpectraMax ® Plus 384 spectrophotometer.…”
Section: Synergy Testing Assaysmentioning
confidence: 99%